A phenomenological interpretation of consciousness and psychoanalytic illustration of unconscious motives in Stephen King’s Misery and Pet Sematary - Sarah, Rumnaz Binte Islam (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2019.